Critical discourse analysis of gastronomy in digital media: Edit Value Modeling for sustainable culinary tourism in Bangkalan - Moch. Imron Rosyidi; Ahmad Cholil; Tatag Handaka; Muhtar Wahyudi; Drajat Wicaksono (Digital Theory, Culture & Society, 2026)
This study examines the discursive construction of Madurese gastronomy and develops the Edit Value Model as a conceptual framework for sustainable culinary tourism. Although Madura possesses a rich culinary heritage, including bebek songkem, tajin sobbih, and kaldu kokot, its gastronomic identity remains overshadowed by other regional tourism icons. Using Critical Discourse Analysis (CDA), the study investigates how gastronomy is constructed and negotiated across three types of digital media: mainstream, independent, and alternative. Data were collected through textual analysis of digital media articles, in-depth interviews with key stakeholders, and field observations in Bangkalan Regency. The findings reveal that digital mainstream media legitimize gastronomy as official heritage aligned with institutional tourism agendas, whereas digital independent media emphasize lifestyle, creativity, and everyday experiences. Digital alternative media, by contrast, combine promotion with critique by exposing socio-economic inequalities and forms of resistance. These discursive practices position digital media as “editors of meaning,” selectively amplifying, marginalizing, or reframing culinary values. The proposed Edit Value Model conceptualizes this process as a dynamic cycle encompassing cultural input, media editing practices, legitimization, lifestyle framing, and reflexivity. The study argues that sustainable culinary tourism depends on discursive justice, ensuring the inclusive representation of community voices alongside institutional interests.